Rapid preparation of rodent testicular cell suspensions and spermatogenic stages purification by flow cytometry using a novel blue-laser-excitable vital dye - Rodríguez-Casuriaga, Rosana (MethodsX, 2014)
Availability of purified or highly enriched fractions representing the various spermatogenic stages is a usual requirement to study mammalian spermatogenesis at the molecular level. Fast preparation of high quality testicular cell suspensions is crucial when flow cytometry (FCM) is chosen to accomplish the stage/s purification. Formerly, we reported a method to rapidly obtain good quality rodent testicular cell suspensions for FCM analysis and sorting. Using that method we could distinguish and purify early meiocytes (leptotene/zygotene stages, L/Z) from more advanced ones (pachytene, P) in guinea pig, which presents an unusually high content of early stages. Here we present an upgrade of that method with improvements that enabled the obtainment of high-purity meiotic substages also from mouse testis, namely: • Shortening of the mechanical disaggregation time to optimize the integrity of the suspension. • Elimination of the 25 μm-filtration step to ensure the presence of large P cells. • Inclusion of a non-cytotoxic, DNA-specific, 488 nm-excitable vital fluorochrome (Vybrant DyeCycle Green [VDG], Invitrogen) instead of Hoechst 33342 (requires UV laser, which can damage nucleic acids) or propidium iodide (usually related to dead/damaged cells). As far as we know, this is the first report on the use of this fluorochrome for the discrimination and purification of meiotic prophase I substages.